Influence of Entrepreneurship Learning and Double Track Programs Increasing Interest in Entrepreneurship - Lailatul Magfiroh; Heru Totok Tri Wahono (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The problem of employing high school graduates is a problem that continues to occur every year, espec, the lack of experience and skills means that high school graduates have the highest poverty rate. East Java provincial government data for 2020 states that around 116,772 high school students did not continue to college and competed with graduates of vocational schools who make up the largest workforce. With these conditions, in 2018 the East Java Provincial Government, in collaboration with the East Java Education Service, launched a high school program called Double Track, this program aims to improve students' entrepreneurial skill. . The purpose of this research is to explain the influence of Entrepreneurship Learning and the Double track Program on Efforts to Increase Student Entrepreneurial Interest . This research is a type of quantitative research. The subjects of this research were 56 students of the Bareng State High School double track program. The sampling technique is purposive sampling technique. The data collection technique uses a questionnaire. Data analysis techniques use validity tests, reliability tests, classic assumption tests consisting of normality tests, multicollinearity tests. heteroscedasticity test, multiple linear regression analysis and hypothesis testing using t-test and f-test. The results of research at SMA Negeri Bareng show (R Square) of 0.136, namely 13.6% and a calculated F value of 6.519676 with Sig. is 0.020 or P < 0.05, then the variable is Entrepreneurship Learning (X1), Double track Program (X2) Student Entrepreneurial Interest (Y).